The Position of Creditors Holding Fiduciary Securities in Bankruptcy - Triyanto, Toni; Widodo, Hendro; Osman, Ahmed Kheir (Jurnal Daulat Hukum, 2025)
Fiduciary is a transfer of ownership of a certain object by juridical levering from the original owner (debtor) to complete a debt agreement to the new owner based on trust alone (creditor), which is essentially a guarantee for the debtor's debt. On the other hand, the object remains under the debtor's control. The problem that occurs in a bankruptcy case is that in the settlement of bankruptcy assets, creditors holding fiduciary guarantees have the authority to execute their rights, as if bankruptcy had not occurred. The aim of writing this article is to analyze the settlement of bankruptcy assets to avoid regulatory conflicts between the Curator and Separatist Creditors. This type of research is normative legal research, namely legal research carried out by solving legal issues and at the same time providing prescriptions. It is prescriptive in nature, where it is legal research. That the position of separatist creditors in the bankruptcy process will take priority even if a bankruptcy occurs. This is stated in Article 27 paragraph (3) of the Fiduciary Guarantee Law which clearly states that priority rights are not extinguished even if bankruptcy occurs and Article 21 of the Mortgage Rights Law which states that the rights of separatist creditors are not lost in the event of bankruptcy and one of the rights Separatist creditors have the right to precede other creditors as stated in Article 20 paragraph (1) of the Mortgage Rights Law.